Analyzing the Efficacy of Topical Ciprofloxacin Ear Drops vs. Oral Tablets and Topical Ciprofloxacin Ear Drops Together for the Treatment of Patients with Chronic Suppurative Otitis Media (CSOM-Tubotympanic Type) - Tanveer, Muhammad Ali, Arshad Saeed Awan, Azam Khan, Ali Zaki, Muhammad Mudassir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: A suppurative Middle ear infection is the most frequent kind of otitis externa in low-income regions of the world (CSOM). Suppurative otitis media (CSOM-tubo tympanic type) affects both young and old alike. The condition has been treated using a wide range of approaches. Objectives: The purpose of this study was to evaluate the efficacy of oral and topical ciprofloxacin against topical ciprofloxacin drops alone in the treatment of CSOM-tubo tympanic ear discharge. Methods: Randomization was used in our study Patients with chronic suppurative otitis media were seen between September 2020 and September 2021 at tertiary care hospital in Peshawar. SPSS version 24 was used to evaluate hospital and pathology lab data. Results: Overall, 75 patients were included in the study's findings. They split themselves into two categories. There were 38 people [group A] and 37 people [ group B]. each Group was classified into two age groups, the younger [ages 01–12] and the older (ages 13–60). (age 13-16 years). Patients' ages ranged from 1 to 12 years old, with 28 [group-A] at 72% and 25 [group-B] at 65%. Ten people 27% in [group-A] and thirteen patients (35%) in [group B], were between the ages of thirteen and sixteen (group B). Conclusions: As a result, we found that the combination of oral and topical ciprofloxacin was superior to topical ciprofloxacin alone in resolving ear discharge in patients with middle ear CSOM (tubo-tympanic type). Keywords: Topical and oral ciprofloxacin, treat chronic suppurative, otitis media